The association between objectively measured physical activity and health-related quality of life, life-space mobility and successful ageing in older Indian adults - Jeanne M. Grace; Jacqueline Naiker (AOSIS, 2022)
Background: Longevity is increasing, accompanied by a rise in disability and chronic diseases with physical activity (PA) delaying disability, ensuring successful ageing (SA) and independent living in older adults. Aim: This study aimed to determine objectively measure PA levels, health-related quality of life (HRQoL), life-space mobility and SA of older adults as well as their mutual associations. Setting: KwaZulu-Natal province, South Africa. Methods: A total of 210 older adults aged 65-92 years were purposively sampled and completed the Medical Outcomes Study 36-Item Short-Form Health Survey, the Life-Space Mobility, and Successful Ageing questionnaires. Physical activity levels were measured using an Omron Pedometer, which the participants wore for seven consecutive days. Results: The average number of steps taken per day for the 7 days was 2025, with 98.6% of the entire study population classified as sedentary. The Vitality domain (one of 8 categorised) reflected the best health status (M = 59.9, s.d. ± 18.8) with a significant 93% of the participants indicating that they had not visited places outside their immediate neighbourhood (p 0.0005). A significant, negative association between the average number of steps taken in 7 days and all three SA variables, namely, the physical (r = -0.152, p = 0.027), sociological (r = -0.148, p = 0.032) and psychological (r = -0.176, p = 0.010), and a significant, positive association with life-space mobility (r = 0.224, p = 0.001) was noted. Conclusion: The majority of the older adults were sedentary, affecting their HRQoL, life-space mobility, and SA negatively. Contribution: It is imperative to develop effective physical activity programmes to ensure successful ageing by improving older adults' quality of life and physical activity levels.